2008
DOI: 10.1038/bjp.2008.198
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐convulsive and anti‐epileptic properties of brivaracetam (ucb 34714), a high‐affinity ligand for the synaptic vesicle protein, SV2A

Abstract: Background and purpose: Screening of 12 000 compounds for binding affinity to the synaptic vesicle protein 2A (SV2A), identified a high-affinity pyrrolidone derivative, brivaracetam (ucb 34714). This study examined its pharmacological profile in various in vitro and in vivo models of seizures and epilepsy, to evaluate its potential as a new antiepileptic drug. Experimental approach: The effects of brivaracetam and levetiracetam on epileptiform activity and seizure expression were examined in rat hippocampal sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
221
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(227 citation statements)
references
References 26 publications
5
221
0
1
Order By: Relevance
“…(BRV) is a selective, high-affinity ligand for synaptic vesicle protein 2A (Gillard et al, 2011) that is effective in different animal models of epilepsy (Matagne et al, 2008). In patients with photosensitive epilepsy, BRV showed a dose-dependent effect in suppressing or attenuating the photoparoxysmal response (Kasteleijn-Nolst Trenite et al, 2007).…”
Section: Brivaracetam [(2s)-2-[(4r)-2-oxo-4-propylpyrrolidinyl] Butanmentioning
confidence: 99%
“…(BRV) is a selective, high-affinity ligand for synaptic vesicle protein 2A (Gillard et al, 2011) that is effective in different animal models of epilepsy (Matagne et al, 2008). In patients with photosensitive epilepsy, BRV showed a dose-dependent effect in suppressing or attenuating the photoparoxysmal response (Kasteleijn-Nolst Trenite et al, 2007).…”
Section: Brivaracetam [(2s)-2-[(4r)-2-oxo-4-propylpyrrolidinyl] Butanmentioning
confidence: 99%
“…If seizures are not fully controlled with benzodiazepines, second-line AEDs such as phenytoin/fosphenytoin, sodium valproate, lacosamide, [3] or the SV2A AED levetiracetam (LEV) are used [4]. brivaracetam (BRV) is an analog of LEV, rationally designed to have a higher affinity and selectivity for SV2A, a protein involved in synaptic vesicle exocytosis and neurotransmitter release [5,6]. Brivaracetam chemically is a 4-npropyl analog of levetiracetam and a racetam derivative with anticonvulsant properties [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…More generally, it will be of interest to assess the role of pharmacological modulation of SV2A in antiepileptogenesis. In this context it is noteworthy that the selective, high-affinity SV2A ligand brivaracetam shows more pronounced antiepileptogenic effects than levetiracetam in the kindling model [57].…”
Section: Levetiracetammentioning
confidence: 99%
“…In support of this possibility, numerous studies have demonstrated that levetiracetam counteracts the process of kindling when administrated immediately before kindling stimulation during the acquisition of kindling [14,15,[54][55][56][57]. As for valproate (see above), levetiracetam was tested using an experimental design consisting of a first phase in which drug treatment is administered before each kindling stimulation, and a second phase in which daily kindling stimulation is continued, but without drug pretreatment [14,15].…”
Section: Levetiracetammentioning
confidence: 99%